Os anos mudam mas o efeito continua o mesmo em todos os meses de janeiro? Uma análise de sazonalidade e do fluxo financeiro dos fundos de ações brasileiros. - Grossi, Janaína Cássia (2018)
Based on the assumption that seasonal patterns were identified in the return of stock markets’ assets and also in the performance of investment funds, the objective of our research is to investigate the relationship between the seasonality “January Effect” and mutual fund’s inflow and outflow from Brazil. The sample of the study consists of 1010 mutual funds during the period January/2004 to June/2018. The results were estimated through multiple linear regression analysis with panel data. We suggest that fund’s net cash flow in January is on average higher than the net cash flow in other months of the year; and also that the effect of the month January on net cash flow is different among Exclusive and Non-Exclusive funds. The study has practical implications for fund managers, investors and policymakers in the sense that it offers better understanding of the behavior of financial market investors, highlights a set of variables that fund managers may be aware to prevent variations in the financial flow of mutual funds in order to reduce its negative effects on performance and also to avoid transaction costs. As far as we are concerned, this study was the first to investigate the effects of the seasonality presented in the month of January on mutual funds’ cash flow in the Brazilian context.